Caregivers’ Experience of Decision-Making regarding Diagnostic Assessment following Cognitive Screening of Older Adults - Jamie J. Y. Lee; Joanna Barlas; Claire L. Thompson; Yan Hong Dong (Journal of Aging Research)
Targeted screening for dementia among older adults in primary healthcare has potential benefits such as better clinical outcomes and the opportunity to access services. Cognitive screening can be followed up by further diagnostic assessment to determine a diagnosis of dementia. Unfortunately, the rates of accepting further diagnostic assessment following cognitive screening are low. The objective of this study was to explore the caregivers’ decision-making process regarding uptake of diagnostic assessment following positive screening results. A qualitative design was employed, and interpretative phenomenological analysis was used to analyze the data. Three major themes in caregiver decision-making were identified: gathering information, protecting the patient, and balancing obligation and convenience in caregiving. These findings suggest that the decision-making process involved effort to process information through observations of the patient and that caregivers emphasized quality of life.